PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN, KEPERCAYAAN DAN LOYALITAS PELANGGAN RETAIL ONLINE DI INDONESIA - Deddy Rahwandi Rahim (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This research was conducted with the aim to: (1) To analyze the effect of service quality on customer satisfaction (Customer Satisfaction) on online retail; (2) To analyze the effect of service quality on customer loyalty (Customer loyalty) in online retail; (3) To analyze the effect of the quality of services to the Trust (the Trust) in online retail; (4) To analyze the effect of customer satisfaction (Customer Satisfaction) of the Trust (the Trust) in online retail; (5) To analyze the effect of customer satisfaction (Customer Satisfaction) on customer loyalty (Customer loyalty) in online retail; (6) To analyze the influence of Trust (the Trust) on customer loyalty (Customer loyalty) in online retail. This study uses primary data through surveys as many as 390 respondents. The survey was conducted from December 2014 until February 2015. Data were analyzed by using the program Structural Equation Modeling (SEM). Results of this study indicate that: (1) Quality of service provide a significant and positive effect on online retail customer satisfaction. (2) The quality of service provides a positive and significant influence on customer loyalty online retail. (3) The quality of service provides a positive and significant effect on customer confidence online retail. (4) Customer satisfaction has positive and significant impact on customer confidence online retail. (5) Customer satisfaction and significant positive effect on customer loyalty online retail. (6) The trust of customers give positive and significant impact on customer loyalty online retail.